Efektivitas Pembelajaran Fikih Menggunakan Media YouTube di Kelas 9 SMA Ardaniah - Sugianto, Relly; Norman, Efrita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
YouTube serves as a tool for managing and delivering information with the aim of manipulating data. This research aims to evaluate the effect of using YouTube as an effective means of learning Islamic Religious Education. The research uses a qualitative approach and is conducted at Ardaniah High School. Data collection methods involve observation, interviews, and documentation. Data analysis is carried out using data reduction techniques, comparing interview results with other data. Research findings include: (1) The process of learning Islamic Religious Education can be simplified to facilitate searching, manipulation, management, and exchange of information; (2) Development of Information and Communication Technology (ICT) skills to enhance the smoothness of learning; (3) Improvement of teachers' professionalism in using YouTube, especially in the context of Islamic Religious Education; and (4) Transformation of schools into creative and dynamic learning institutions, stimulating students' motivation to always be curious in learning Islamic Religious Education. Effective learning requires careful planning, including the selection of appropriate learning media. The use of YouTube as a learning support tool has proven to be very effective in the context of Islamic Religious Education in the technological era, especially at Ardaniah High School.